1994
DOI: 10.1021/jf00043a002
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State 13C NMR Investigation of Molecular Ordering in the Cellulose of Apple Cell Walls

Abstract: A resolution-enhanced 13C nuclear magnetic resonance (NMR) spectrum of cell wall material isolated from Braeburn apples has revealed a pair of signals assigned to cellulose chains exposed on crystal surfaces, providing evidence for a high degree of molecular ordering on those surfaces. Proton spin relaxation editing revealed no detectable amorphous cellulose and provided an estimate of about 23 chains in a typical crystallite. Cellulose in apple cell walls was found to be distinctive, with triclinic and monocl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 31 publications
5
61
2
Order By: Relevance
“…These signal assignments follow Newman et al (1994). The values of T,(C) fall below the range 15 to 25 s observed for C-4 of cellulose in secondary cell walls of the wood of the dicotyledon Eucalyptus delegatensis and the gymnosperm Pinus radiata (Newman, 1992).…”
Section: T(h)supporting
confidence: 51%
See 3 more Smart Citations
“…These signal assignments follow Newman et al (1994). The values of T,(C) fall below the range 15 to 25 s observed for C-4 of cellulose in secondary cell walls of the wood of the dicotyledon Eucalyptus delegatensis and the gymnosperm Pinus radiata (Newman, 1992).…”
Section: T(h)supporting
confidence: 51%
“…10a) showed a pair of peaks 84.0 and 85.1 ppm, assigned to C-4 in chains exposed on crystallite surfaces. These peaks were resolved in earlier studies of cellulose (Newman, 1994;Newman et al, 1994), and the relative heights were found to be independent of the relative proportions of I, and I, forms (Newman, 1994). The pair of peaks has therefore been assigned to pairs of crystallographically nonequivalent sites on well-ordered crystallite surfaces, regardless of whether the interior is in the I, or I, form .…”
Section: Crystal Formsmentioning
confidence: 78%
See 2 more Smart Citations
“…Solid-state NMR spectroscopy of cellulose produces doublet d 13 C4 peaks that have been used to estimate the degree of crystallinity of cellulose as well as the number of glucan chains in elementary cellulose microfibrils (Kennedy et al 2007;Newman et al 1994Newman et al , 1996Park et al 2009;Teeäär et al 1987;Wang et al 2015). Two d 13 C4 peaks, centered at * 89 and * 85 ppm, have been assigned to ordered (crystalline) and disordered (amorphous) regions, respectively (Atalla et al 1980;Earl and VanderHart 1980).…”
Section: Introductionmentioning
confidence: 99%